Intelektual Muslim Baru yang Menetas Semasa Orde Baru - Nanang Tahqiq (Refleksi: Jurnal Kajian Agama dan Filsafat, 1999)
The main thesis of this book is that during the New Order era, a unique and distinct Islamic intellectual movement emerged, known as Neo-Modernism. Nurcholish Madjid, Djohan Effendi, the late Ah. Mad Wahib, and Abdurrahman Wahid are four figures of this Neo-Modernist movement. The hallmark of their intellectual movement lies in their mastery of classical/traditional Islamic knowledge (commonly referred to as "kitab kuning") combined with modern knowledge. The characteristic of integrating these two forms of knowledge did not emerge in the period from pre-independence until the 1970s. In the past, those educated in modern sciences lacked mastery of Islamic teachings, while those well-versed in Islamic sciences were not adaptive to modern knowledge. This situation consequently gave rise to two popular typologies: the first group known as Modernists (represented by Masyumi, Muhammadiyah, and Western-educated Muslim scholars), while the second group is referred to as Traditionalists (represented by NU and students lacking Western education). Even among intellectuals of the past who possessed both aspects, they were very few in number. The late Harun Nasution, Mukti Ali, and Mohammad Natsir were among those few.